Risk management in the higher education quality insurance system - Kondić, Živko (Array, 2020)
Due to the factors that affect the results of work on a daily basis, higher education institutions, through their quality assurance systems, or their planning, must assess risks. In doing so, they must take into account all issues of the internal and external context as well as the needs and expectations of all stakeholders in higher education. The paper explains in an appropriate way the concept of risk as well as all the elements that determine it and their classification in the field of higher education. Subsequently, a possible approach to risk management is discussed, with an emphasis on clarifying the principles and the risk management process itself. Finally, the basics of practical application in risk identification, analysis, evaluation and treatment are outlined.